The Newly concepts in Children Treatment with Chronic Diseases in Primary Health Care - Mohammed Haji Al Briman; Zuhair Abdullah Almuhnna; Mustafa Ali Alhajji; Abdulhadi Nazar Alhaji; Abdulah Eissa Almuani; Sara Ayish Alherz; Habeeb Saleh Alsalman; Salwa Ali Alrizq; Hussain Jawad Aljassem; Munther Saleh Alkhmees; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Most of the significant chronic illnesses that affect children and adolescents are characterized by an acute phase surrounding the diagnosis of the illness followed by prolonged stress associated with extended treatment, recovery, and survivorship. Each phase of a chronic illness can present children and their families with significant challenges and stressors. However, there is evidence that chronic conditions may exert greater psychological and physical stress than acute illnesses that resolve quickly [4]. Further, many pediatric illnesses are exacerbated by stress encountered in other aspects of children’s lives, here arises the role of family physicians (FPs) to help the child and their parents understand the ways that children cope with stress to better explicate processes of adaptation to illness and to develop effective interventions to enhance coping and adjustment(Compas et al., 2012)[5].Children with disabilities or chronic illnesses are at increased risk for psychological morbidity[6]. In particular, psychological maladjustment is 10–15% higher in children with chronic conditions, as compared to healthy controls[7]. Finally, the Ontario Child Health Study reported that children with chronic conditions and major disability were three times more likely to have a psychiatric disorder than their healthy counterparts, controlling for age and sex-specific risks for psychiatric problems[8].Potential interactions between the burdens on the family that result from a child’s chronic illness and family members’ psychological morbidity are hypothesized to explain the associations with child’s psychological morbidity.